2015
DOI: 10.1002/jms.3698
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐induced dissociation (EID) for structure characterization of glycerophosphatidylcholine: determination of double‐bond positions and localization of acyl chains

Abstract: Glycerophospholipids are a highly abundant and diverse collection of biologically relevant lipids and distinction between isomeric and isobaric species is a fundamental aspect for confident identification. The ability to confidently assign a unique structure to a glycerophospholipid of interest is dependent on determining the number and location of the points of unsaturation and assignment of acyl chain position. The use of high energy electrons (>20 eV) to induce gas-phase dissociation of intact precursor ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 42 publications
(57 reference statements)
11
71
0
1
Order By: Relevance
“…This cleavage has not been observed by CID, and only infrequently in high energy EID (26) and metastable atom activation (27). This peak solves permutation of two chains at sn-1 and sn-2 (Table 2).…”
Section: Resultsmentioning
confidence: 86%
“…This cleavage has not been observed by CID, and only infrequently in high energy EID (26) and metastable atom activation (27). This peak solves permutation of two chains at sn-1 and sn-2 (Table 2).…”
Section: Resultsmentioning
confidence: 86%
“…A number of fragmentation approaches, including HCD, multistage CID, charge remote fragmentation, and charge transfer dissociation have been explored for this purpose, but have shown limited capabilities [35]. Recently, several novel fragmentation approaches have shown great promise for efficient C=C determination, including electron transfer dissociation (ETD) [36], helium metastable atom activated dissociation (He-MAD) [37,38], electron impact excitation of ions from organics (EIEIO)/electron-induced dissociation (EID) [39,40], radical-directed dissociation (RDD) [41] and ultraviolet photodissociation (UVPD) [42,43]. ETD and He-MAD utilize ions reactions with radical anions metastable or helium atoms to induce similar radical-based fragmentation pathways.…”
Section: Fragmentation Approaches and Ion-molecule Reactions To Determentioning
confidence: 99%
“…[24] The odd-electron fragments in Fig. 2(c) were also observed in MAD [12] and EID [24] spectra of the same lipid, which suggests analogous fragmentation pathways among CTD, MAD and EID. The odd-electron fragments must be generated via the introduction of radical species during the fragmentation process, indicating the involvement of radical cleavages in CTD.…”
Section: Resultsmentioning
confidence: 65%
“…[10,21,24] In contrast to this general preference for sn-2 ketene loss over sn-1 ketene loss, Ho and Huang show no such preference for sn-2 ketene loss in low-energy CID experiments in a quadrupole ion trap [16] and Jones et al observed a slight preference for sn-1 ketene loss over sn-2 ketene loss in the EID fragmentation of phospholipids. [24] The odd-electron fragments in Fig. 2(c) were also observed in MAD [12] and EID [24] spectra of the same lipid, which suggests analogous fragmentation pathways among CTD, MAD and EID.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation